2020
DOI: 10.2196/15895
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Web-Based, Patient-Centered Intervention for Patients With Chronic Myeloid Leukemia (CMyLife): Design Thinking Development Approach

Abstract: Background With the global rise in chronic health conditions, health care is transforming, and patient empowerment is being emphasized to improve treatment outcomes and reduce health care costs. Patient-centered innovations are needed. We focused on patients with chronic myeloid leukemia (CML), a chronic disease with a generally good long-term prognosis because of the advent of tyrosine kinase inhibitors. However, both medication adherence by patients and guideline adherence by physicians are subop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…Of the clinical studies, four studies were of low quality [ 37 , 41 , 43 , 44 ], three of moderate quality [ 38 , 39 , 42 ], and one study was assessed as a high-quality study [ 40 ]. Regarding the barrier and facilitator studies, three studies were of low quality [ 49 , 51 , 53 ], one of moderate quality [ 48 ], and five were of high quality [ 45 - 47 , 50 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the clinical studies, four studies were of low quality [ 37 , 41 , 43 , 44 ], three of moderate quality [ 38 , 39 , 42 ], and one study was assessed as a high-quality study [ 40 ]. Regarding the barrier and facilitator studies, three studies were of low quality [ 49 , 51 , 53 ], one of moderate quality [ 48 ], and five were of high quality [ 45 - 47 , 50 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite these barriers, three studies showed that the use of a digital care platform is feasible [ 40 , 42 , 44 ]. Facilitators in practice were numerous: access to general and tailored medical information [ 42 , 45 , 47 - 49 , 52 ], full EMRs [ 39 , 42 , 45 - 48 , 50 - 52 ], and educational materials [ 42 , 47 ]. Moreover, the possibility to consult HCPs through interactive tools was mentioned to be a positive feature of a digital care platform that encouraged usage [ 43 , 44 , 47 , 48 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations